Adhesive composition and adhesive sheet

By using a specific proportion of alkyl acrylate monomer and isocyanate-based hardener in the adhesive composition, the problem of reducing adhesion and insufficient releasability of the acrylic-based adhesive under high temperature or humid heat conditions is solved, and high temperature is achieved full repellency and adhesion underneath.

CN119213093APending Publication Date: 2024-12-27아티엔스가부시키가이샤 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040841.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-02
Filing Date
2023-05-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The conventional acrylic adhesive composition is prone to residual when peeled off under high temperature or humidity conditions, and the releasability is insufficient, especially when the adhesion force is reduced at high temperature, making it difficult to ensure sufficient releasability.

Method used

The adhesive formed by adjusting the monomer content and gel fraction are adjusted by using a copolymer containing an alkyl acrylate monomer having an alkyl carbon number of 1 to 12, a monomer having an acidic group and a hydroxyl group. The composition has high adhesion and good releasing properties.

Benefits of technology

The full releasability under high temperature or humidity conditions is achieved, the adhesive protrudes at high temperature is reduced, the long-term storage stability and adhesion of the adhesive sheet is ensured, and the applicability of the adhesive is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005136570550000221
    Figure BDA0005136570550000221
  • Figure BDA0005136570550000241
    Figure BDA0005136570550000241
  • Figure BDA0005136570550000251
    Figure BDA0005136570550000251
Patent Text Reader

Abstract

The present invention provides an adhesive composition and an adhesive sheet, comprising: an acrylate copolymer which is a copolymer of a monomer mixture comprising an alkyl (meth) acrylate monomer, a monomer having an acidic group, and a monomer having a hydroxyl group; and an isocyanate-based curing agent, the adhesive composition and the adhesive sheet having sufficient adhesive force and high viscosity, exhibiting good re-peelability, and having little extension of the adhesive from the sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition and an adhesive sheet. Background Art

[0002] An adhesive sheet having an adhesive layer formed of an adhesive is easier to handle than an adhesive, and is therefore used in a wide range of fields as a display label or a fixing tape, and is generally divided into a strong adhesive type for permanent fixing and a re-peelable type for peeling off the adhesive sheet after use. As adhesives, there are various resin-based adhesives, among which acrylic acid is widely used. Acrylic acid-based adhesives have the following advantages, that is, it is easy to control the basic adhesive properties such as adhesive force or adhesion by adjusting the monomer composition or compatible additives.

[0003] As a re-peelable acrylic adhesive, Patent Document 1 discloses an adhesive composition characterized by comprising an acrylic adhesive layer, wherein the acrylic adhesive layer is formed by crosslinking an acrylic polymer having a (meth)acrylic acid alkyl ester having an alkyl group with 4 to 12 carbon atoms as a main component monomer and copolymerizing the acrylic polymer with at least 3 to 20% by weight of free radical polymerizable monomers containing carboxyl groups in the total monomers, using a crosslinking agent having a functional group reactive with a carboxyl group in the molecule at a gel fraction of 80% by weight or more. In addition, Patent Document 2 discloses a removable adhesive sheet, characterized in that an adhesive layer is provided on one side of a substrate, and the adhesive layer is formed by coating an adhesive composition comprising a tackifying resin and a crosslinking agent, which comprises a heat-expandable microsphere, a weight-average molecular weight of 100,000 to 300,000, an acrylic adhesive that can react with a crosslinking agent and has an acid value of 30 or more, and a softening point of 90° C. or more and a solubility parameter value (solubility parameter, SP value) of 8.9 or more.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2000-328016

[0007] Patent Document 2: Japanese Patent Application Publication No. 2003-160765 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the adhesive composition of Patent Document 1 has the following problem: when the adhesive sheet is peeled off after being stored for a long time under high temperature or hot and humid conditions while being attached to an adherend, the adhesive remains on the adherend. In addition, regarding the adhesive sheet of Patent Document 2, it is difficult to ensure sufficient removability under conditions at room temperature, and there is a peeling problem accompanied by a decrease in adhesive strength under conditions of high temperature, or a problem of insufficient removability after long-term storage at high temperature.

[0010] Therefore, the problem to be solved by the embodiments of the present invention is to provide the following adhesive composition and adhesive sheet, which have sufficient adhesive force and high viscosity, show good re-peelability even for high-polarity adherends such as SUS and steel plates where the adhesive is easy to remain when peeled off, and have sufficient re-peelability when stored for a long time under high temperature or humid heat conditions in an attached state. In addition, even in an attached state under high temperature and high load conditions, the adhesive protrudes little from the sheet, and even at high temperature, heavy adherends such as steel plates can be overlapped and stored.

[0011] Technical means of solving problems

[0012] In order to solve the above-mentioned problems, the present inventors have found the following adhesive composition, which comprises: an acrylate copolymer, which is a copolymer of a monomer mixture comprising a (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group; and an isocyanate-based hardener, wherein the content of the monomer (B) having an acidic group is 0.01% by mass or more and 6% by mass or less in 100% by mass of the monomer mixture, the content of the monomer (C) having a hydroxyl group is 0.05% by mass or more and 10% by mass or less in 100% by mass of the monomer mixture, and the gel fraction is 55% or more.

[0013] That is, the present disclosure includes the following embodiments [1] to [4].

[0014] [1] An adhesive composition comprising: an acrylate copolymer, wherein the acrylate copolymer is a copolymer of a monomer mixture comprising a (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group; and an isocyanate hardener,

[0015] The content of the (meth)acrylic acid alkyl ester monomer (a1) having an alkyl group with 8 to 12 carbon atoms in 100% by mass of the (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms is 55% by mass or more and 90% by mass or less,

[0016] The content of the monomer (B) having an acidic group is 0.01% by mass or more and 6% by mass or less in 100% by mass of the monomer mixture,

[0017] The content of the monomer (C) having a hydroxyl group is 0.05% by mass or more and 10% by mass or less in 100% by mass of the monomer mixture,

[0018] The isocyanate curing agent includes a trimethylolpropane adduct of toluene diisocyanate.

[0019] The gel fraction is 55% or more.

[0020] [2] The adhesive composition according to [1], wherein the value of the ratio (P) of the loss elastic coefficient at 25°C to the loss elastic coefficient at 150°C when measured at 1 Hz represented by Formula 1 is 0.02 or more and 0.3 or less.

[0021] P = (loss elastic coefficient at 150°C when measured at 1 Hz) / (loss elastic coefficient at 25°C when measured at 1 Hz) (Formula 1)

[0022] [3] The adhesive composition according to [1] or [2], wherein the value of the ratio (P) of the loss elastic coefficient at 25°C to the loss elastic coefficient at 150°C when measured at 1 Hz represented by Formula 1 is greater than or equal to 0.03 and less than or equal to 0.15.

[0023] P = (loss elastic coefficient at 150°C when measured at 1 Hz) / (loss elastic coefficient at 25°C when measured at 1 Hz) (Formula 1)

[0024] [4] An adhesive sheet comprising a substrate and an adhesive layer comprising a cured product of the adhesive composition according to any one of [1] to [3].

[0025] Effects of the Invention

[0026] According to some embodiments, the following adhesive composition and adhesive sheet can be provided, which have sufficient adhesive force and high viscosity, show good re-peelability even for high-polarity adherends such as SUS and steel plates on which the adhesive is likely to remain when peeled, and have sufficient re-peelability when stored for a long time under high temperature or humid heat conditions in an attached state. In addition, even in an attached state under high temperature and high load conditions, the adhesive protrudes little from the sheet, and heavy adherends such as steel plates can be overlapped and stored even at high temperatures. DETAILED DESCRIPTION

[0027] Below, the details of the present invention are described. In addition, as long as it meets the purpose of the present invention, other embodiments are certainly also included in the scope of the present invention. In addition, the numerical range determined by using "~" in this specification includes the numerical values ​​recorded before and after "~" as the range of the lower limit and upper limit.

[0028] In this specification, when "(meth)acrylic acid" or "(meth)acrylate" is expressed, it means "acrylic acid or methacrylic acid" or "acrylate or methacrylate", respectively, unless otherwise specified. In addition, the so-called "(meth)acrylate monomer" is a general term for "acrylate monomer" and "methacrylate monomer". In addition, the (meth)acrylate alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms is sometimes simply described as monomer (A), the monomer (B) having an acidic group is simply described as monomer (B), and the monomer (C) having a hydroxyl group is simply described as monomer (C).

[0029] In this specification, "Mw" is the weight average molecular weight in terms of polystyrene determined by gel permeation chromatography (GPC). "Mn" is the number average molecular weight in terms of polystyrene determined by GPC. These can be measured by the method described in [Examples].

[0030] Unless otherwise specified, various components mentioned in the present specification may be used alone or in combination of two or more.

[0031] <Acrylate copolymer>

[0032] The acrylic acid ester copolymer refers to a polymer of a monomer having an ethylenically unsaturated bond such as a (meth)acrylic acid ester monomer.

[0033] The acrylic acid ester copolymer in some embodiments is a copolymer of a monomer mixture containing at least a (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group, wherein the content of the monomer (B) having an acidic group is 0.01% by mass or more and 6% by mass or less in 100% by mass of the monomer mixture, and the content of the monomer (C) having a hydroxyl group is 0.05% by mass or more and 10% by mass or less in 100% by mass of the monomer mixture.

[0034] The monomers are classified into (meth)acrylic acid alkyl ester monomers (A) having an alkyl group with 1 to 12 carbon atoms, monomers (B) having an acidic group, monomers (C) having a hydroxyl group, and other monomers. Monomers constituting the acrylic ester copolymer include monomers (A), (B), and (C) as essential components, and other monomers may be used as necessary.

[0035] [Monomer (A)]

[0036] Monomer (A) is an alkyl (meth)acrylate monomer having an alkyl group with 1 to 12 carbon atoms. As alkyl (meth)acrylate monomers having an alkyl group with 1 to 12 carbon atoms, they are classified into alkyl (meth)acrylate monomers having 8 to 12 carbon atoms (a1) and alkyl (meth)acrylate monomers having 1 to 7 carbon atoms (a2). It is preferred to use an alkyl (meth)acrylate monomer having 8 to 12 carbon atoms (a1), and it is more preferred to use (a1) and (a2) in combination. By using an alkyl (meth)acrylate monomer having 8 to 12 carbon atoms (a1), it is possible to achieve both high levels of adhesion and removability.

[0037] Examples of the monomer (a1) include octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, and lauryl (meth)acrylate. Among these, 2-ethylhexyl (meth)acrylate and lauryl (meth)acrylate are preferred in terms of removability.

[0038] The content of monomer (a1) is not particularly limited, and is preferably 55% by mass or more, more preferably 65% ​​by mass or more, in 100% by mass of the monomer mixture constituting the acrylic ester copolymer. The upper limit is not particularly limited, and if it is forcibly set, it is preferably 90% by mass or less, more preferably 80% by mass or less. By setting it to the above range, high viscosity and re-peelability can be taken into account.

[0039] Examples of the monomer (a2) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, and heptyl (meth)acrylate. Of these, butyl acrylate and (iso)butyl acrylate are preferred in terms of exhibiting good adhesion to various adherends.

[0040] [Monomer (B)]

[0041] The monomer (B) is a monomer having an acidic group. By using the monomer (B), good adhesiveness and cohesiveness can be exhibited on various adherends.

[0042] Examples of the monomer (B) include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl-succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl-phthalic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, citraconic acid, mesaconic acid, and other carboxylic acids having an unsaturated bond, or 2-(meth)acryloyloxyethyl acid phosphate. In terms of the cohesive force of the adhesive composition obtained and the copolymerizability with other monomers, (meth)acrylic acid and 2-carboxyethyl (meth)acrylate are preferred.

[0043] In the monomer mixture 100% by mass constituting the acrylic ester copolymer, the content of monomer (B) is 0.01% by mass and 6% by mass, preferably 0.1% by mass and 4% by mass, more preferably 0.5% by mass and 3.5% by mass, particularly preferably 1% by mass and 3% by mass. By the content of monomer (B) being 0.05% by mass or more, high adhesion and cohesion can be imparted. In addition, by the content of monomer (B) being 6% by mass or less, even if the adhesive sheet is peeled off from the adherend, the adhesion of the adhesive composition to the adherend can be suppressed.

[0044] [Monomer (C)]

[0045] The monomer (C) is a monomer having a hydroxyl group. By using the monomer (C), a reaction site with an isocyanate-based curing agent is provided, and good removability can be imparted even under high temperature or moist heat conditions.

[0046] Examples of the monomer having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, and hydroxy(meth)acrylamides such as hydroxymethacrylamide and hydroxyethylacrylamide. From the viewpoint of reactivity with an isocyanate-based curing agent and the cohesive force obtained, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred.

[0047] In 100% by mass of the monomer mixture constituting the acrylic ester copolymer, the content of the monomer (C) is 0.05% by mass or more and 10% by mass or less, preferably 0.07% by mass or more and 1.8% by mass or less, and more preferably 0.08% by mass or more and 1% by mass or less. When the content of the monomer (C) is 0.05% by mass or more, high cohesive force can be imparted during the reaction of the hardener. When the content of the monomer (B) is 10% by mass or less, a significant increase in the viscosity of the solution after the hardener is prepared can be suppressed, and good re-peelability can be imparted.

[0048] [Other monomers]

[0049] Other monomers are monomers other than the monomer (A), the monomer (B) and the monomer (C). The other monomers are not particularly limited, and monomers copolymerizable with the monomers (A), (B), and (C) can be appropriately selected, and examples thereof include carboxylic acid vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl butyrate, other vinyl monomers such as styrene and acrylonitrile, monomers having an alicyclic structure such as isobornyl (meth)acrylate and cyclohexyl (meth)acrylate, monomers having an aromatic ring such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and biphenyl (meth)acrylate, monomers having an alkoxy (poly) alkylene oxide such as 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, and ethoxypolypropylene glycol (meth)acrylate, acid anhydrides having polymerizable unsaturated bonds in the molecule such as maleic anhydride and itaconic anhydride, monomers having an amino group, other monomers having a nitrogen atom, monomers having an epoxy group, and monomers having an isocyanate group.

[0050] Examples of the monomer having an amino group include monoalkylamino (meth)acrylates such as monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, and monoethylaminopropyl (meth)acrylate.

[0051] As other monomers having a nitrogen atom, (meth)acrylamide, N-vinyl pyrrolidone, acryloylmorpholine, etc. are mentioned.

[0052] As a monomer which has an epoxy group, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3, 4-epoxycyclohexylmethyl (meth)acrylate, 6-methyl-3, 4-epoxycyclohexylmethyl (meth)acrylate, etc. are mentioned, for example.

[0053] As a monomer which has an isocyanate group, 2-isocyanatoethyl (meth)acrylate etc. are mentioned, for example.

[0054] [Method for producing acrylic acid ester copolymer]

[0055] There is no particular limitation on the method for producing the acrylic ester copolymer, and the monomer mixture can be polymerized by a known free radical polymerization reaction. The reaction can be carried out without a solvent, but from the viewpoint of synthetic stability and operation, it is preferred to use a solvent. In addition, from the viewpoint of molecular weight control, it is preferred to use a free radical polymerization initiator (hereinafter, sometimes referred to as a "polymerization initiator"). In addition, known additives such as chain transfer agents can also be used.

[0056] As the solvent, the solvent described below can be used.

[0057] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide, or 2,2'-azobisisobutyronitrile, 2, Azo compounds such as 2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0058] Examples of the chain transfer agent include alkyl mercaptans such as octyl mercaptan, nonyl mercaptan, decyl mercaptan, and dodecyl mercaptan, thioglycolates such as octyl thioglycolate, nonyl thioglycolate, and 2-ethylhexyl thioglycolate, 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, and β-pinene. In particular, thioglycolates, 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, and β-pinene are preferred in terms of low odor of the obtained polymer.

[0059] The weight average molecular weight Mw of the acrylic ester copolymer is preferably 200,000 to 2,000,000, more preferably 300,000 to 1,000,000, further preferably 400,000 to 900,000, and particularly preferably 500,000 to 800,000, based on the standard polystyrene conversion value obtained by gel permeation chromatography (GPC). If the weight average molecular weight is 200,000 or more, sufficient cohesive force can be obtained. If the weight average molecular weight is 2,000,000 or less, the increase in viscosity can be suppressed, and good coating adaptability can be obtained.

[0060] The molecular weight dispersion Mw / Mn of the acrylic acid ester copolymer is preferably 2.0 to 12, more preferably 4 to 10, in terms of standard polystyrene obtained by gel permeation chromatography (GPC). When the molecular weight dispersion is within the above range, both adhesive force and cohesive force can be achieved. In addition, Mn refers to the number average molecular weight.

[0061] The glass transition temperature (Tg) of the acrylic acid ester copolymer is not particularly limited, but is preferably -70°C to -25°C, and more preferably -65°C to -30°C. If the glass transition temperature is -70°C or higher, sufficient cohesive force can be obtained. If the glass transition temperature is -25°C or lower, good adhesive force can be exhibited.

[0062] In addition, in some embodiments, the glass transition temperature (Tg) of the acrylic ester copolymer (A) is a value calculated based on the following (Formula 2) (Fox formula).

[0063] 1 / Tg=W1 / Tg1+W2 / Tg2+…+Wn / Tgn (Formula 2)

[0064] [In formula (2), Tg represents the Tg (unit: K) of the acrylic ester copolymer (A), Tgi (i=1, 2, ...n) represents the Tg (unit: K) when the radical polymerizable monomer i forms a homopolymer, and Wi (i=1, 2, ...n) represents the mass fraction of the radical polymerizable monomer i in all monomer components. In addition, the Tg of the homopolymer is a published value such as a literature value or a catalog value]

[0065] The formula (2) is a calculation formula when the acrylic ester copolymer (A) includes monomer 1, monomer 2, ..., monomer n, these n monomer components.

[0066] <Isocyanate hardener>

[0067] The adhesive composition in some embodiments includes an isocyanate hardener as a hardener. The isocyanate hardener forms crosslinking points with the monomer (C) having a hydroxyl group included in the acrylic copolymer, thereby exhibiting high adhesiveness and cohesiveness.

[0068] Examples of the isocyanate curing agent include: compounds having three or more isocyanate groups in the molecule such as toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylene diisocyanate, hydrogenated xylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate, adducts with polyol compounds such as trimethylolpropane, and biuret forms thereof, and isocyanurate forms thereof, and adducts of the above diisocyanates with any of polyols such as polyether polyol, polyester polyol, acrylic polyol, polybutadiene polyol, and polyisoprene polyol; or compounds having two isocyanate groups in the molecule such as alloformates thereof. Among these, trimethylolpropane adducts of toluene diisocyanate, trimethylolpropane adducts of xylene diisocyanate, and trimethylolpropane adducts of hexamethylene diisocyanate are preferred because their adhesive properties can be easily adjusted, and trimethylolpropane adducts of toluene diisocyanate are particularly preferred. In addition, the number of isocyanate groups is an average number.

[0069] The content of the isocyanate curing agent is not particularly limited, but is preferably 0.1 to 10 parts by mass, more preferably 1 to 9 parts by mass, and particularly preferably 1.5 to 7 parts by mass, relative to 100 parts by mass of the acrylic ester copolymer. If the content of the isocyanate curing agent is 0.1 parts by mass or more, sufficient cohesive force can be obtained, and if it is 10 parts by mass or less, shaking during peeling can be suppressed.

[0070] The adhesive composition in some embodiments may further use other hardeners other than isocyanate hardeners. Other hardeners include metal chelate hardeners, epoxy hardeners, or aziridine hardeners. By including these hardeners, the cohesive force of the adhesive composition is further improved, and the heat resistance is improved.

[0071] As the metal chelate-based hardener, known compounds can be used, for example, coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium and ligands such as acetylacetone and ethyl acetoacetate, etc. From the viewpoint of long-term storage stability, the polyvalent metal is preferably aluminum, and the ligand is preferably at least one of acetylacetone and ethyl acetoacetate.

[0072] Examples of the metal chelate curing agent include aluminum alkoxides such as aluminum isopropoxide, aluminum mono-sec-butoxydiisopropoxide, aluminum sec-butoxide, and aluminum ethoxide;

[0073] Aluminum chelates such as aluminum acetoacetate diisopropoxide, aluminum tris(acetoacetate), aluminum acetoacetate alkyl ester diisopropoxide, aluminum monoacetoacetate bis(acetoacetate), aluminum tris(acetylacetonate),

[0074] Titanium alkoxides such as titanium tetraisopropoxide, titanium tetra-n-butyloxide, titanium butoxide dimer, and titanium tetra-2-ethylhexyloxide,

[0075] Titanium chelates such as isopropoxybis(acetylacetonate), titanium tetraacetylacetonate, diisopropoxybis(ethyl acetoacetate), titanium phosphate complex, and titanium octanediol,

[0076] Zirconium alkoxides such as zirconium tetrapropoxide and zirconium tetrabutoxide,

[0077] Zirconium chelates such as zirconium tetraacetylacetonate, zirconium tributoxymonoacetylacetonate, zirconium tetraacetylacetonate, and zirconium dibutoxybis(ethyl acetoacetate),

[0078] Zirconium acylate such as zirconium stearate.

[0079] Among these, alkyl acetoacetate aluminum diisopropoxide, bis(ethyl acetoacetate)aluminum monoacetoacetate, and aluminum tris(acetylacetonate) are preferred in terms of crosslinking properties, adhesive strength, transparency, and storage stability.

[0080] Examples of the epoxy curing agent include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, N,N,N',N'-tetraglycidyl-m-xylene diamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.

[0081] Examples of the aziridine curing agent include N,N'-diphenylmethane-4,4'-bis(1-aziridine carboxide), N,N'-toluene-2,4-bis(1-aziridine carboxide), bisisophthaloyl-1-(2-methylaziridine), tris-1-aziridinylphosphine oxide, N,N'-hexamethylene-1,6-bis(1-aziridine carboxide), 2,2'-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate], trimethylolpropane tris-β-aziridinylpropionate, tetramethylolmethane tris-β-aziridinylpropionate, and tris-2,4,6-(1-aziridinyl)-1,3,5-triazine.

[0082] The content of the other curing agent is not particularly limited, but is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, based on 100 parts by mass of the acrylic ester copolymer.

[0083] In order to increase the pot life of the adhesive, a known catalyst action inhibitor may be added to the adhesive composition in some embodiments.

[0084] Specific examples of the catalyst action inhibitor include keto-enol tautomer forming compounds, etc. The keto-enol tautomer forming compound is a compound that can form keto-enol tautomers, and preferably acetylacetone, acetoacetate, malonic acid ester, etc.

[0085] Examples of the acetoacetate include methyl acetoacetate, ethyl acetoacetate, isopropyl acetoacetate, butyl acetoacetate, isobutyl acetoacetate, and tert-butyl acetoacetate.

[0086] Examples of the malonic acid ester include dimethyl malonate, diethyl malonate, and dibutyl malonate.

[0087] Among these, the keto-enol tautomer-forming compound is preferably acetylacetone in terms of volatility during drying.

[0088] The content of the catalyst inhibitor is preferably 0.05 to 10.0 parts by mass, more preferably 0.1 to 5.0 parts by mass, and even more preferably 0.5 to 3.0 parts by mass, relative to 100 parts by mass of the acrylic ester copolymer. If the amount of the catalyst inhibitor is 0.05 parts by mass or more, the pot life is good, and if it is 10.0 parts by mass or less, good initial curability can be obtained.

[0089] <Solvent>

[0090] The adhesive composition in some embodiments may include a solvent.

[0091] There is no particular restriction on the timing of preparing the solvent. It can be used in the manufacture of the acrylic ester copolymer or as a diluent solvent for adjusting the viscosity in the manufacture of the adhesive composition. The solvent can be selected based on the leveling and drying properties during coating, as well as the effects on the environment and human body. The solvent is preferably an aliphatic hydrocarbon, an alicyclic hydrocarbon, an aromatic hydrocarbon, an ester, a ketone, an alcohol, etc.

[0092] Examples of the solvent include ester solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone, methyl butyl ketone, and cyclohexanone; hydrocarbon solvents such as toluene, xylene, and anisole; and alcohol solvents such as methanol, ethanol, n-propanol, and isopropanol. From the perspective of the pot life of the adhesive composition, it is preferred to contain an ester solvent and / or an alcohol solvent.

[0093] The amount of the solvent used is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, based on 100 parts by mass of the acrylic ester copolymer. The upper limit is not particularly limited, but is preferably 2000 parts by mass or less from the viewpoint of coating properties.

[0094] <Adhesive resin>

[0095] The adhesive composition in some embodiments may further include an adhesion imparting resin. The adhesion imparting resin can be used by any method such as a method used during solution polymerization, a method of being deployed in an acrylate copolymer, etc. If the adhesion imparting resin is used during solution polymerization, it acts as a chain transfer agent and is easy to adjust the molecular weight of the acrylate copolymer. In addition, if it is deployed in an acrylate copolymer, the adhesion can be further improved.

[0096] The softening point of the tackifier resin is preferably 70°C to 170°C, more preferably 75°C to 160°C, and still more preferably 100°C to 150°C.

[0097] When the softening point of the adhesion-imparting resin is within the above range, it is easy to achieve both adhesion and cohesive force at a high level. The softening point is a softening temperature measured by the dry bulb method specified in Japanese Industrial Standards (JIS) SK5902.

[0098] As the adhesion imparting resin, it is not limited to the following examples, and can be listed: rosin resin, polymerized rosin resin, rosin ester resin, polymerized rosin ester resin, terpene resin, terpene phenol resin, coumarone resin, coumarone-indene resin, styrene resin, xylene resin, phenol resin, petroleum resin, etc. Among these, with respect to good compatibility with acrylate copolymer (A) and further improving adhesion performance, rosin resin, polymerized rosin resin, rosin ester resin and polymerized rosin ester resin, petroleum resin, styrene resin are preferably used. One kind of adhesion imparting resin can be used alone, and two or more kinds can also be used in combination.

[0099] The content of the tackifier resin is preferably 1 to 60 parts by mass, more preferably 1.5 to 20 parts by mass, and further preferably 2 to 10 parts by mass, relative to 100 parts by mass of the acrylic ester copolymer. By adding 1 part by mass or more of the tackifier resin, the adhesive force can be increased, and by setting it to 60 parts by mass or less, the removability can be maintained.

[0100] <Plasticizer>

[0101] In order to suppress the shaking during peeling, the adhesive composition in some embodiments may further contain a plasticizer as needed. The plasticizer is not particularly limited, but is preferably an organic acid ester from the viewpoint of compatibility with the acrylic ester copolymer.

[0102] Examples of the esters of monobasic or polybasic acids and alcohols include isostearyl laurate, isopropyl myristate, isocetyl myristate, octyldodecyl myristate, isostearyl palmitate, isocetyl stearate, octyldodecyl oleate, dibutyl phthalate, dioctyl phthalate, diheptyl phthalate, dibenzyl phthalate, butylbenzyl phthalate, diisodecyl adipate, diisostearyl adipate, dibutyl sebacate, diisocetyl sebacate, acetyl tributyl citrate, tributyl trimellitate, trioctyl trimellitate, trihexyl trimellitate, trioleyl trimellitate, and triisocetyl trimellitate.

[0103] Examples of other esters of acids and alcohols include esters of unsaturated fatty acids or branched acids such as myristic acid, oleic acid, linoleic acid, linolenic acid, isopalmitic acid, and isostearic acid, and alcohols such as ethylene glycol, propylene glycol, glycerin, trimethylolpropane, pentaerythritol, and sorbitan.

[0104] Examples of the ester of a monobasic acid or polybasic acid with a polyalkylene glycol include polyethylene glycol dihexylate, polyethylene glycol di-2-ethylhexylate, polyethylene glycol dilaurate, polyethylene glycol dioleate, and polyethylene glycol dimethyl adipate.

[0105] Examples of the phosphate ester plasticizer include tricresyl phosphate (TCP), triphenyl phosphate (TPP), tri-2-ethylhexyl phosphate (TOP), trixylenyl phosphate (TXP), and triethyl phosphate (TEP).

[0106] Examples of the epoxy plasticizer include epoxidized soybean oil, epoxidized linseed oil, epoxidized octyl stearate, epoxidized fatty acid butyl ester, and epoxidized linseed oil fatty acid butyl ester.

[0107] The molecular weight (formula weight or Mn) of the plasticizer is preferably 250 to 1000, more preferably 400 to 900, and particularly preferably 500 to 850. When the molecular weight is 250 or more, the heat resistance of the adhesive layer becomes good, and when the molecular weight is 1000 or less, a sufficient chatter suppression effect can be obtained.

[0108] The content of the plasticizer is not particularly limited, but is preferably 0.01 to 30 parts by mass, more preferably 4 to 20 parts by mass, relative to 100 parts by mass of the acrylic ester copolymer. If the content of the plasticizer is 0.01 parts by mass or more, a sufficient effect of suppressing vibration during peeling can be obtained, and if it is 30 parts by mass or less, a decrease in adhesive force can be suppressed.

[0109] <Antioxidants>

[0110] The adhesive composition in some embodiments may further include an antioxidant as needed.

[0111] As antioxidants, free radical scavengers and peroxide decomposers can be mentioned. As free radical scavengers, phenolic compounds and amine compounds can be mentioned. As peroxide decomposers, sulfur compounds and phosphorus compounds can be mentioned.

[0112] Examples of the phenolic compound include 2,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, stearyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4'-butylenebis(3-methyl-6-tert-butylphenol), 3,9-bis[1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5, 5] undecane, phenylpropionic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, C7-C9 side chain alkyl ester, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-tert-butylphenyl)butyric acid]ethylene glycol ester, 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, and tocopherol, etc.

[0113] Examples of the sulfur-based antioxidant include dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, and distearyl 3,3'-thiodipropionate.

[0114] Examples of the phosphorus compound include triphenyl phosphite, diphenyl isodecyl phosphite, 4,4'-butylene-bis(3-methyl-6-tert-butylphenyl di-tridecyl)phosphite, cyclic neopentanetetraylbis(octadecylphosphite), tris(nonylphenyl)phosphite, tris(monononylphenyl)phosphite, tris(dinonylphenyl)phosphite, diisodecyl pentaerythritol diphosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(3,5- 10-decyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-decyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene, tris(2,4-di-tert-butylphenyl)phosphite, cyclic neopentanetetraylbis(2,4-di-tert-butylphenyl)phosphite, cyclic neopentanetetraylbis(2,6-di-tert-butyl-4-methylphenyl)phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octylphosphite.

[0115] By using an antioxidant, thermal degradation of the acrylic ester copolymer can be prevented and heat resistance can be improved.

[0116] The amount of the antioxidant added is not particularly limited, but is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, and still more preferably 0.2 to 2 parts by mass, based on 100 parts by mass of the acrylic acid ester copolymer.

[0117] As the antioxidant, a phenolic compound as a radical scavenger is preferred in terms of transparency and polymerization inhibition effect. The phenolic compound can effectively suppress the residual monomer components during the synthesis of the acrylic ester copolymer (A) from generating low molecular weight components in the subsequent step and reducing heat resistance.

[0118] The adhesive composition in some embodiments may further be formulated with known additives such as catalysts, antistatic agents (AS agents), ultraviolet absorbers, light stabilizers, lubricants, corrosion inhibitors, heat stabilizers, weather stabilizers, anti-hydrolysis agents, mildew inhibitors, thickeners, fillers (talc, calcium carbonate, and titanium oxide, etc.), silane coupling agents, polymerization inhibitors, defoamers, slip agents, anti-caking agents, anti-fogging agents, lubricants, dyes, waxes, emulsions, magnetic bodies, and dielectric properties adjusters as needed.

[0119] Adhesive composition

[0120] The adhesive composition in some embodiments comprises: an acrylate copolymer, which is a copolymer of a monomer mixture comprising a (meth) alkyl acrylate monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group; and an isocyanate curing agent. In addition, the content of the monomer (B) having an acidic group is 0.01% by mass or more and 6% by mass or less in 100% by mass of the monomer mixture, the content of the monomer (C) having a hydroxyl group is 0.05% by mass or more and 10% by mass or less in 100% by mass of the monomer mixture, and the gel fraction is 55% or more.

[0121] <Gel fraction>

[0122] The gel fraction is a value calculated from the following (Formula 3).

[0123] (Gel fraction) = {(W2-W0-W3) / (W1-W0-W3)}×100 (Formula 3)

[0124] W0: Weight of the metal mesh

[0125] W1: Weight of metal mesh + test piece

[0126] W2: Weight of metal mesh + test piece after drying

[0127] W3: Weight of the test piece substrate

[0128] The method for measuring the gel fraction is described in detail in the section of Examples.

[0129] The gel fraction of the adhesive composition in some embodiments is 55% or more and 100% or less, preferably 70% or more and 98% or less, and more preferably 80% or more and 95% or less. When the gel fraction is 55% or more, good removability can be exhibited even after storage at high temperature.

[0130] <Viscoelasticity>

[0131] Regarding the storage elastic coefficient (G'), loss elastic coefficient (G"), and loss tangent (tanδ) of the adhesive layer formed by the adhesive composition in some embodiments, the temperature dependence was measured using a viscoelasticity measuring device "Ares-G2" manufactured by TA Instruments (stock company) under the conditions of frequency: 1 Hz, strain 0.1%, temperature: -50°C to 200°C (heating rate 10°C / min), and the values ​​at 25°C and 150°C were used.

[0132] In the adhesive composition of some embodiments, the value of the ratio (P) of the loss elastic coefficient at 25°C and the loss elastic coefficient at 150°C when measured at 1 Hz represented by Formula 1 is 0.02 or more and 0.3 or less, preferably 0.03 or more and 0.15 or less, more preferably 0.04 or more and 0.07 or less, and particularly preferably 0.05 or more and 0.06 or less. When the value of (P) is within the above range, good adhesion and adhesion can be exhibited during attachment, and good re-peelability can be exhibited even when attached for a long time under high temperature conditions, and the extension of the adhesive can be suppressed even when a load is applied at high temperature.

[0133] (P) = (loss elastic coefficient at 150°C when measured at 1 Hz) / (loss elastic coefficient at 25°C when measured at 1 Hz) (Formula 1)

[0134] The storage elastic coefficient (G') at 25°C of the adhesive layer formed from the adhesive composition of the present invention is not particularly limited, but is preferably 15,000 Pa or more and 90,000 Pa or less, and more preferably 30,000 Pa or more and 65,000 Pa or less. When it is 15,000 Pa or more, sufficient cohesive force can be obtained, and when it is 90,000 Pa or less, good adhesive force can be obtained during use.

[0135] The storage elastic coefficient (G') at 150°C of the adhesive layer formed from the adhesive composition of the present invention is not particularly limited, but is preferably 10,000 Pa or more and 50,000 Pa or less. When it is 15,000 Pa or more, an adhesive with little stretching can be obtained even at high temperatures, and when it is 50,000 Pa or less, good adhesion can be obtained even at high temperatures.

[0136] The loss elastic coefficient (G") at 25°C of the adhesive layer formed from the adhesive composition of the present invention is not particularly limited, but is preferably 10,000 Pa or more and 40,000 Pa or less, and more preferably 15,000 Pa or more and 30,000 Pa or less. When it is 10,000 Pa or more, sufficient adhesive force and adhesion can be obtained, and when it is 40,000 Pa or less, good removability can be obtained during use.

[0137] The loss elastic coefficient (G") at 150°C of the adhesive layer formed from the adhesive composition of the present invention is not particularly limited, but is preferably 800 Pa or more and 8,000 Pa or less, and more preferably 900 Pa or more and 2,500 Pa or less. When it is 800 Pa or more, sufficient adhesive force and adhesion can be obtained even at high temperatures, and when it is 8,000 Pa or less, good removability can be obtained even at high temperatures.

[0138] <Method for producing adhesive composition>

[0139] The method for producing the adhesive composition of the present invention is not particularly limited. The adhesive composition in some embodiments can be produced by adding an isocyanate curing agent, a solvent, and optionally, any components to an acrylic ester copolymer and mixing them.

[0140] The non-volatile component concentration of the adhesive composition in some embodiments is preferably 30% to 75% by mass, more preferably 38% to 65% by mass, and further preferably 40% to 60% by mass. By setting the non-volatile component concentration of the adhesive composition to a high level, the content of the solvent can be relatively suppressed, thereby suppressing the drying cost during application and suppressing the load on the environment and the human body.

[0141] The viscosity of the adhesive composition at 25°C is preferably 1,000mPa·s to 20,000mPa·s, more preferably 1,500mPa·s to 10,000mPa·s, and further preferably 2,500mPa·s to 7,000mPa·s. When the viscosity of the adhesive composition is within the above range, the coating property is improved, and it is easy to obtain an adhesive layer with a smooth surface. In addition, the viscosity is the viscosity measured at 25°C using a BL type viscometer, with a #3 rotor and a rotation speed of 12 rpm, 1 minute after the start of rotation.

[0142] "Adhesive Film"

[0143] The adhesive sheet comprises a substrate and an adhesive layer of a cured product comprising the adhesive composition of the present invention. The adhesive layer can be formed on one side or both sides of the substrate. Optionally, the exposed surface of the adhesive layer can be coated with a release sheet. In addition, the release sheet is peeled off when the adhesive sheet is pasted on an adherend.

[0144] When the adhesive composition is applied, the viscosity may be adjusted using the above-mentioned solvent, or the adhesive composition may be heated to reduce the viscosity.

[0145] The substrate is not particularly limited, and examples thereof include resin sheets, paper, and metal foil. The substrate may be a laminated sheet having one or more layers laminated on at least one surface of these substrates. Optionally, the surface of the substrate on which the adhesive layer is formed may be subjected to corona discharge treatment and anchor coating agent coating, etc., to facilitate adhesion treatment.

[0146] The constituent resin of the resin sheet is not particularly limited, and examples thereof include: ester resins such as polyethylene terephthalate (PET); olefin resins such as polyethylene (PE) and polypropylene (PP); vinyl resins such as polyvinyl chloride; amide resins such as nylon 66; urethane resins (including foams); combinations of these, etc.

[0147] The thickness of the resin sheet other than the polyurethane sheet is not particularly limited, but is preferably 15 μm to 300 μm. The thickness of the polyurethane sheet (including the foam) is not particularly limited, but is preferably 20 μm to 50000 μm.

[0148] The paper is not particularly limited, and examples thereof include plain paper, coated paper, and coated paper.

[0149] The constituent metal of the metal foil is not particularly limited, and examples thereof include aluminum, copper, and combinations thereof.

[0150] The release sheet is not particularly limited, and a known release sheet can be used in which a known release treatment such as coating a release agent on the surface of a base sheet such as a resin sheet or paper is performed.

[0151] The adhesive sheet can be produced by a known method.

[0152] First, the adhesive composition of the present invention is applied to the surface of the substrate to form a coating layer comprising the adhesive composition of the present invention. The coating method can be a known method, including a roll coater method, a notch wheel coater method, a die coater method, a reverse coater method, a screen printing method, and a gravure coater method.

[0153] Next, the coating layer is dried and cured to form an adhesive layer comprising a cured product of the adhesive composition of the present invention. The heating and drying temperature is not particularly limited, but is preferably about 60° C. to 150° C. The thickness of the adhesive layer (thickness after drying) varies depending on the application, but is preferably 0.1 μm to 200 μm.

[0154] Next, a release sheet is attached to the exposed surface of the adhesive layer by a known method as necessary.

[0155] As described above, a single-sided pressure-sensitive adhesive sheet can be produced.

[0156] By performing the above operation on both sides, a double-sided adhesive sheet can be produced.

[0157] In contrast to the above method, the adhesive composition of the present invention may be coated on the surface of the release sheet to form a coating layer comprising the adhesive composition of the present invention, and the coating layer may be dried and cured to form an adhesive layer comprising a cured product of the adhesive composition of the present invention, thereby laminating a substrate sheet on the exposed surface of the adhesive layer.

[0158] The manufacturing method of the adhesive sheet preferably includes: a coating step of coating an adhesive on a substrate; a heating step of heating and drying the formed coating layer to form an adhesive layer of a cured product containing the adhesive composition; a winding step of winding the obtained adhesive sheet on a winding core to form an adhesive sheet roll; and a curing step of curing the adhesive sheet roll.

[0159] Example

[0160] Hereinafter, synthesis examples, examples of the present invention, and comparative examples will be described. In the following description, unless otherwise specified, "parts" means parts by mass, "%" means mass %, and "RH" means relative humidity.

[0161] [Measurement of weight average molecular weight (Mw)]

[0162] The weight average molecular weight (Mw) is measured by gel permeation chromatography (GPC). The measurement conditions are as follows. In addition, Mw is a polystyrene conversion value.

[0163] <Measurement conditions>

[0164] Equipment: LC-GPC system "Prominence" manufactured by Shimadzu Corporation,

[0165] String: 4 GMHXL made by Tosoh, 1 HXL-H made by Tosoh, connected in series

[0166] Detector: Differential refractive index detector (RID-10A),

[0167] Solvent: tetrahydrofuran (THF),

[0168] Flow rate: 1mL / min,

[0169] Solvent temperature: 40℃,

[0170] Sample concentration: 0.2%,

[0171] Sample injection volume: 100μL

[0172] <Manufacturing of acrylic acid ester copolymer>

[0173] (Synthesis example 1)

[0174] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 17.2 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 790,000.

[0175] (Synthesis example 2)

[0176] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 4-hydroxybutyl acrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 4-hydroxybutyl acrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 17.2 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 770,000.

[0177] (Synthesis example 3)

[0178] Into a reaction vessel (hereinafter, sometimes referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.84 parts of 2-carboxyethyl acrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction vessel was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a vessel A including a stirrer, and 16.4 parts of butyl acrylate, 1.96 parts of 2-carboxyethyl acrylate, and 5 parts of ethyl acetate were placed in a vessel B. Then, the reaction vessel was heated to 80°C while stirring in a nitrogen atmosphere. After the reaction started, the contents of container A were dripped in over 2 hours using a drip pump. At this time, the contents of container B were simultaneously supplied to container A over 2.0 hours while stirring. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the reaction was cooled and diluted by adding ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. In addition, the weight average molecular weight (Mw) of the acrylate copolymer was 820,000.

[0179] (Synthesis Example 4)

[0180] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 7.2 parts of butyl acrylate, 10 parts of ethyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring under a nitrogen atmosphere, and after the reaction started, the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 880,000.

[0181] (Synthesis Example 5)

[0182] Into a reaction vessel (hereinafter, sometimes referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 12 parts of 2-ethylhexyl acrylate, 7.5 parts of isononyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction vessel was replaced with nitrogen. Furthermore, 28 parts of 2-ethylhexyl acrylate, 17.5 parts of isononyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a vessel A including a stirrer, and 17.2 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in a vessel B. Then, the reaction vessel was heated to 80°C while stirring in a nitrogen atmosphere. After the reaction started, the contents of container A were dripped in over 2 hours using a drip pump. At this time, the contents of container B were simultaneously supplied to container A over 2.0 hours while stirring. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the reaction was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. In addition, the weight average molecular weight (Mw) of the acrylate copolymer was 810,000.

[0183] (Synthesis Example 6)

[0184] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 19.15 parts of butyl acrylate, 0.05 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 800,000.

[0185] (Synthesis Example 7)

[0186] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 18.4 parts of butyl acrylate, 0.8 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 800,000.

[0187] (Synthesis Example 8)

[0188] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 18.2 parts of butyl acrylate, 1 part of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 800,000.

[0189] (Synthesis Example 9)

[0190] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.84 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 16.4 parts of butyl acrylate, 1.96 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 810,000.

[0191] (Synthesis Example 10)

[0192] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 1.05 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 15.7 parts of butyl acrylate, 2.45 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 820,000.

[0193] (Synthesis Example 11)

[0194] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 1.65 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 13 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 15.7 parts of butyl acrylate, 3.85 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 850,000.

[0195] (Synthesis Example 12)

[0196] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.02 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.03 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 17.95 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 790,000.

[0197] (Synthesis Example 13)

[0198] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.04 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.03 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 17.93 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 790,000.

[0199] (Synthesis Example 14)

[0200] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.08 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.07 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 17.85 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 780,000.

[0201] (Synthesis Example 15)

[0202] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.5 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 17.1 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 790,000.

[0203] (Synthesis Example 16)

[0204] Into a reaction container (hereinafter, sometimes referred to as "reaction container") equipped with a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.8 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 0.7 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A equipped with a stirrer, and 16.5 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 790,000.

[0205] (Synthesis Example 17)

[0206] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 35 parts of 2-ethylhexyl acrylate, 11 parts of lauryl methacrylate, 2 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 16 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 810,000.

[0207] (Synthesis Example 18)

[0208] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 65 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 15 parts of 2-ethylhexyl acrylate, 5 parts of lauryl methacrylate, 32.2 parts of butyl acrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 15 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 830,000.

[0209] (Synthesis Example 19)

[0210] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 65 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 15 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 22.2 parts of butyl acrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 10 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 15 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 800,000.

[0211] (Synthesis Example 20)

[0212] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 65 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 22.2 parts of 2-ethylhexyl acrylate, 15 parts of lauryl methacrylate, 15 parts of butyl acrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 10 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 15 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 770,000.

[0213] (Synthesis Example 21)

[0214] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 40 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 34 parts of 2-ethylhexyl acrylate, 5 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 35 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 28.2 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 700,000.

[0215] (Synthesis Example 22)

[0216] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 45 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 15 parts of 2-ethylhexyl acrylate, 42 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 20 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 10.2 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 720,000.

[0217] (Synthesis Example 23)

[0218] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 30 parts of 2-ethylhexyl acrylate, 0.6 parts of acrylic acid, 0.4 parts of 2-hydroxyethyl methacrylate, 40 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 16 parts of 2-ethylhexyl acrylate, 36 parts of lauryl methacrylate, 0.4 parts of 2-hydroxyethyl methacrylate, 5 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in container A including a stirrer, and 10 parts of lauryl methacrylate, 5.2 parts of butyl acrylate, 1.4 parts of acrylic acid, and 5 parts of ethyl acetate were placed in container B. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were added dropwise over 2 hours using a dropping pump. At this time, the contents of container B were simultaneously supplied to container A while stirring for 2.0 hours. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 800,000.

[0219] (Synthesis Example 24)

[0220] Into a reaction vessel (hereinafter, sometimes referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 13.5 parts of 2-ethylhexyl acrylate, 1.5 parts of lauryl methacrylate, 14.2 parts of butyl acrylate, 0.6 parts of acrylic acid, 0.24 parts of 2-hydroxyethyl methacrylate, 50 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction vessel was replaced with nitrogen. Furthermore, 31.5 parts of 2-ethylhexyl acrylate, 3.5 parts of lauryl methacrylate, 33 parts of butyl acrylate, 1.4 parts of acrylic acid, 0.56 parts of 2-hydroxyethyl methacrylate, 30 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a vessel A including a stirrer. Then, the reaction vessel was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of the container A were dripped over 2 hours using a drip pump. The polymerization reaction was carried out at reflux temperature for 8 hours in a nitrogen atmosphere. After the reaction was completed, the solution was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. In addition, the weight average molecular weight (Mw) of the acrylate copolymer was 830,000.

[0221] (Synthesis Example 25)

[0222] Into a reaction vessel (hereinafter, sometimes referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 8.4 parts of 2-ethylhexyl acrylate, 0.9 parts of lauryl methacrylate, 14 parts of butyl acrylate, 6 parts of ethyl acrylate, 0.6 parts of acrylic acid, 0.3 parts of 2-hydroxyethyl methacrylate, 50 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction vessel was replaced with nitrogen. Furthermore, 19.6 parts of 2-ethylhexyl acrylate, 32.9 parts of butyl acrylate, 2.1 parts of lauryl methacrylate, 14 parts of ethyl acrylate, 1.4 parts of acrylic acid, 0.7 parts of 2-hydroxyethyl methacrylate, 30 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a vessel A including a stirrer. Then, the reaction vessel was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of the container A were dripped over 2 hours using a drip pump. The polymerization reaction was carried out at reflux temperature for 8 hours in a nitrogen atmosphere. After the reaction was completed, the solution was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. In addition, the weight average molecular weight (Mw) of the acrylate copolymer was 700,000.

[0223] (Comparative Synthesis Example 1)

[0224] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 13.5 parts of 2-ethylhexyl acrylate, 1.5 parts of lauryl methacrylate, 14 parts of butyl acrylate, 0.8 parts of acrylic acid, 60 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged, and then the air in the reaction container was replaced with nitrogen. Furthermore, 31.5 parts of 2-ethylhexyl acrylate, 33.2 parts of butyl acrylate, 3.5 parts of lauryl methacrylate, 2.0 parts of acrylic acid, 30 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged into a container A including a stirrer. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere, and the reaction was started. The contents of container A were dripped over 2 hours using a drip pump. The polymerization reaction was carried out at reflux temperature for 8 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted by adding ethyl acetate to obtain an acrylate copolymer solution having a nonvolatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 810,000.

[0225] (Comparative Synthesis Example 2)

[0226] Into a reaction container (hereinafter, sometimes referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 13.5 parts of 2-ethylhexyl acrylate, 1.5 parts of lauryl methacrylate, 14 parts of butyl acrylate, 0.6 parts of 2-hydroxyethyl methacrylate, 60 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction container was replaced with nitrogen. Furthermore, 31.5 parts of 2-ethylhexyl acrylate, 34 parts of butyl acrylate, 3.5 parts of lauryl methacrylate, 1.4 parts of 2-hydroxyethyl methacrylate, 30 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a container A including a stirrer. Then, the reaction container was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of container A were dripped over 2 hours using a drip pump. The polymerization reaction was carried out at reflux temperature for 8 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. The weight average molecular weight (Mw) of the acrylate copolymer was 810,000.

[0227] (Comparative Synthesis Example 3)

[0228] Into a reaction vessel (hereinafter, sometimes referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 13.5 parts of 2-ethylhexyl acrylate, 1.5 parts of lauryl methacrylate, 10.5 parts of butyl acrylate, 2.7 parts of acrylic acid, 1.8 parts of 2-hydroxyethyl methacrylate, 55 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction vessel was replaced with nitrogen. Furthermore, 31.5 parts of 2-ethylhexyl acrylate, 24.5 parts of butyl acrylate, 3.5 parts of lauryl methacrylate, 6.3 parts of acrylic acid, 4.2 parts of 2-hydroxyethyl methacrylate, 15 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a vessel A including a stirrer. Then, the reaction vessel was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of the container A were dripped over 2 hours using a drip pump. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the solution was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. In addition, the weight average molecular weight (Mw) of the acrylate copolymer was 880,000.

[0229] (Comparative Synthesis Example 4)

[0230] Into a reaction vessel (hereinafter, sometimes referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 13.5 parts of 2-ethylhexyl acrylate, 1.5 parts of lauryl methacrylate, 9.3 parts of butyl acrylate, 1.2 parts of acrylic acid, 4.5 parts of 2-hydroxyethyl methacrylate, 55 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction vessel was replaced with nitrogen. Furthermore, 31.5 parts of 2-ethylhexyl acrylate, 21.7 parts of butyl acrylate, 3.5 parts of lauryl methacrylate, 2.8 parts of acrylic acid, 10.5 parts of 2-hydroxyethyl methacrylate, 10 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a vessel A including a stirrer. Then, the reaction vessel was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of the container A were dripped over 2 hours using a drip pump. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the solution was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. In addition, the weight average molecular weight (Mw) of the acrylate copolymer was 850,000.

[0231] (Comparative Synthesis Example 5)

[0232] Into a reaction vessel (hereinafter, sometimes referred to as "reaction vessel") including a stirrer, a thermometer, a reflux cooling tube, and a nitrogen inlet tube, 13.5 parts of 2-ethylhexyl acrylate, 1.5 parts of lauryl methacrylate, 7.8 parts of butyl acrylate, 2.7 parts of acrylic acid, 4.5 parts of 2-hydroxyethyl methacrylate, 55 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed, and then the air in the reaction vessel was replaced with nitrogen. Furthermore, 31.5 parts of 2-ethylhexyl acrylate, 18.2 parts of butyl acrylate, 3.5 parts of lauryl methacrylate, 6.3 parts of acrylic acid, 10.5 parts of 2-hydroxyethyl methacrylate, 10 parts of ethyl acetate, and 0.02 parts of 2,2'-azobisisobutyronitrile (AIBN) were placed in a vessel A including a stirrer. Then, the reaction vessel was heated to 80°C while stirring in a nitrogen atmosphere to start the reaction, and the contents of the container A were dripped over 2 hours using a drip pump. The polymerization reaction was carried out at reflux temperature under a nitrogen atmosphere for 8 hours. After the reaction was completed, the solution was cooled and diluted with ethyl acetate to obtain an acrylate copolymer solution having a non-volatile content of 35%. In addition, the weight average molecular weight (Mw) of the acrylate copolymer was 870,000.

[0233] [Table 1]

[0234]

[0235] The abbreviations described in Table 1 are shown below.

[0236] 2EHA: 2-Ethylhexyl acrylate

[0237] INA: Isononyl acrylate

[0238] LMA: Lauryl Methacrylate

[0239] EA: Ethyl acrylate

[0240] BA: Butyl acrylate

[0241] AA: Acrylic acid

[0242] BCEA: 2-carboxyethyl acrylate

[0243] HEMA: 2-Hydroxyethyl Methacrylate

[0244] 4HBA: 4-Hydroxybutyl acrylate

[0245] (Example 1)

[0246] <Manufacturing of adhesive composition>

[0247] 2.5 parts of TDI-TMP as an isocyanate curing agent was prepared based on nonvolatile content per 100 parts of the acrylic acid ester copolymer (Synthesis Example 1), and ethyl acetate as a solvent was added so that the nonvolatile content was 30%, and the mixture was uniformly mixed to obtain an adhesive composition.

[0248] <Manufacturing of adhesive sheets>

[0249] The obtained adhesive composition was applied to the peeling treatment surface of a 38 μm thick peelable sheet (made of polyethylene terephthalate, hereinafter referred to as "peelable film substrate") in such a manner that the thickness after drying was 25 μm, and dried in a hot air oven at 100° C. for 90 seconds to prepare an adhesive layer. After drying, it was laminated to a substrate (made of polyethylene terephthalate) with a thickness of 50 μm, and then cured at 23° C.-50% RH for 7 days to obtain an adhesive sheet.

[0250] (Example 2 to Example 32, Comparative Example 1 to Comparative Example 7)

[0251] Each adhesive composition and adhesive sheet were produced by the same method as the adhesive sheet of Example 1 except that the acrylic acid ester copolymer and various additives were changed to the composition and blending amount (parts by mass) of Table 2.

[0252] [Table 2]

[0253]

[0254]

[0255] [Table 3]

[0256] Table 3

[0257]

[0258] The materials used are as follows.

[0259] <Isocyanate hardener>

[0260] TDI-TMP: adduct of toluene diisocyanate and trimethylolpropane

[0261] <Other hardeners>

[0262] Azd: Aziridine hardener, Chemitite PZ-33, manufactured by Japan Catalyst Co., Ltd.

[0263] <Plasticizer>

[0264] ATBC: Acetyl tributyl citrate

[0265] [Evaluation items and evaluation methods]

[0266] The obtained adhesive composition and adhesive sheet were used to perform evaluation according to the following method.

[0267] (Gel fraction)

[0268] After coating, a test piece with a width of 30 mm and a length of 100 mm was cut from the adhesive sheet after curing for 7 days in an environment of 23°C-50% RH. The peeling sheet was peeled off from the test piece, and the exposed adhesive layer was attached to a 300-mesh stainless steel metal mesh. The metal mesh was folded to prevent the test piece from peeling off, and the test piece was immersed in ethyl acetate while being wrapped, and allowed to stand at 50°C for 24 hours. After immersion, the metal mesh was taken out, washed with a small amount of ethyl acetate, dried at 100°C for 30 minutes, and the weight was measured. The gel fraction was calculated by the following (Formula 3).

[0269] (Gel fraction) = {(W2-W0-W3) / (W1-W0-W3)}×100 (Formula 3)

[0270] W0: Weight of the metal mesh

[0271] W1: Weight of metal mesh + test piece

[0272] W2: Weight of metal mesh + test piece after drying

[0273] W3: Weight of the test piece substrate

[0274] (Viscoelasticity)

[0275] The adhesive composition obtained is applied to the peeling treatment surface of a 38 μm thick peelable sheet (made of polyethylene terephthalate, hereinafter referred to as "peelable film substrate") in a manner that the thickness after drying becomes 25 μm, and dried at 100°C for 90 seconds in a hot air oven to prepare an adhesive layer. After drying, it is laminated to another peelable sheet (made of polyethylene terephthalate, hereinafter referred to as "peelable film substrate") with a thickness of 75 μm, and cured for 7 days in an environment of 23°C-50% RH to prepare an adhesive layer sandwiched by two peelable sheets with a structure of "peelable sheet / adhesive layer / peelable sheet". Subsequently, a single peelable sheet is peeled off, and the adhesive layers are repeatedly stacked in an overlapping manner to obtain an adhesive layer with a thickness of 1 mm. After removing bubbles using an autoclave, the test piece for measuring the storage elastic coefficient is demolded into a cylindrical shape with a diameter of 8 mm, and the peelable sheets on both sides are peeled off, and the viscoelasticity is measured. Regarding the storage elastic coefficient (G'), loss elastic coefficient (G"), and loss tangent (tanδ) of the adhesive layer, the temperature dependence was measured using the viscoelasticity measuring device "Ares-G2" manufactured by TA Instruments (stock) at a frequency of 1 Hz, a strain of 0.1%, and a temperature of -50°C to 200°C (heating rate of 10°C / min). Using the obtained loss elastic coefficient (G") values ​​at 25°C and 150°C, the value of P was calculated according to the following (Formula 1).

[0276] P = (loss elastic coefficient at 150°C when measured at 1 Hz) / (loss elastic coefficient at 25°C when measured at 1 Hz) (Formula 1)

[0277] (Adhesion)

[0278] A test piece of 25 mm in width and 150 mm in length was cut from the adhesive sheet after curing for 5 hours under an environment of 23°C-50%RH. The adhesive layer exposed by peeling off the peelable sheet from the cut adhesive sheet was pasted on the surface of a stainless steel plate (SUS304), and a 2kg roller was reciprocated once and crimped. Afterwards, it was placed in an environment of 23°C-50%RH for 24 hours. Then, according to JISZ0237, a tensile testing machine (tensilon: manufactured by Orientec) was used to measure the adhesion (adhesion before heating) under the conditions of a peeling speed of 300 mm / min and a peeling angle of 180°. The evaluation criteria are as follows.

[0279] [Evaluation criteria]

[0280] ◎: 3N / 25mm or above, excellent.

[0281] ○: 1 N / 25 mm or more and less than 3 N / 25 mm, good.

[0282] △: 0.6N / 25mm or more and less than 1N / 25mm, practical.

[0283] ×: Less than 0.6N / 25mm, not practical.

[0284] (Rolling ball adhesion)

[0285] Prepare the obtained adhesive sheet with a size of 25mm in width and 250mm in length. Peel off the peelable sheet from the adhesive sheet and fix it on an inclined plate with an inclination angle of 30 degrees with the adhesive surface facing upward. Attach the PET film for the runway to the upper part, roll a steel ball (1 / 32 to 32 / 32 inches) to the sample with a runway of 10cm and an adhesive surface of 10cm, and record the number of the diameter of the ball that stops near the center of the adhesive surface. Perform the measurement in an environment of 23°C and a relative humidity of 50%.

[0286] Evaluation criteria in an environment of 23°C and 50% relative humidity

[0287] ◎: The ball diameter is 11 or more. Very good.

[0288] ○: The ball diameter is 8 to 10. Good.

[0289] △: The ball diameter is 5 to 7. It is practical.

[0290] ×: The ball diameter is 4 or less. Not practical.

[0291] (Repeel Test)

[0292] A test piece of 25 mm in width and 150 mm in length was cut from the adhesive sheet after curing for 7 days under the environment of 23°C-50%RH. The adhesive layer exposed by peeling off the peelable sheet from the cut adhesive sheet was pasted on the surface of the stainless steel plate (SUS304), and the 2kg roller was reciprocated once and crimped. Afterwards, it was kept for 10 days under the environment of 23°C-50%RH, 40°C, 60°C, and 55°C-80%RH. After 10 days, the test piece was placed at 23°C-50%RH for 3 hours, and then according to JISZ0237, a tensile testing machine (tensilon: manufactured by Orientec) was used to measure the adhesion (adhesion before heating) under the conditions of a peeling speed of 300 mm / min and a peeling angle of 180°, and the state of the stainless steel plate after the measurement was observed. The evaluation criteria are as follows.

[0293] [Evaluation criteria]

[0294] ◎: No adhesive adheres to the stainless steel plate, excellent.

[0295] ○: The adhesion of the adhesive to the stainless steel plate exceeded 0% and was less than 3% of the adhesion area, which was good.

[0296] △: The adhesion of the adhesive to the stainless steel plate is 3% or more and less than 5% of the adhesion area, which is practically applicable.

[0297] ×: The adhesive adhered to the stainless steel plate in an amount of 5% or more of the attached area and could not be used.

[0298] (Stretch-out test)

[0299] Prepare an adhesive sheet with a width of 10 mm and a length of 10 mm after curing for 5 hours or 7 days in an environment of 23°C-50% RH. Peel off the peelable sheet from the adhesive sheet, sandwich the upper and lower peelable sheets (made of polyethylene terephthalate) with a thickness of 38 μm, and apply 50 kg / cm2 of pressure at 60°C using a compression tester. 2 After the test, the sample was taken out and the width (maximum value) of the paste extending from the end of the test piece was measured.

[0300] Evaluation Benchmarks

[0301] ◎: The protrusion is less than 0.2 mm. Very good.

[0302] ○: The overhang is 0.2 mm or more and less than 0.4 mm. Good.

[0303] △: The overhang is 0.4 mm or more and less than 0.6 mm. It is practical.

[0304] ×: The overhang is 0.6 mm or more. Not practical.

[0305] (Storage stability)

[0306] After the hardener was prepared, the uniformly mixed adhesive composition was left to stand in an environment of 23° C. and 50% RH, and the viscosity increase rate was calculated according to the following (Formula 4).

[0307] (Rate of increase in viscosity) = {(viscosity 7 days after the hardener is prepared) / (viscosity 1 hour after the hardener is prepared) × 100} (Formula 4)

[0308] [Evaluation criteria]

[0309] ◎: The viscosity increase rate was less than 150%, which was excellent.

[0310] ○: The rate of increase in viscosity is 150% or more and less than 160%, which is good.

[0311] △: The rate of increase in viscosity is 160% or more and less than 170%, which is practically applicable.

[0312] ×: The viscosity increase rate was 170% or more and the product could not be used.

[0313] The adhesive composition of the present invention can be used to produce the following adhesive sheet: the adhesive properties are good, and the removability after long-term storage under various conditions is good, the adhesive sticking out under high temperature and high load is also small, and the storage stability after the hardener is prepared is also excellent. The adhesive composition of the present invention is the following adhesive composition, which comprises: an acrylate copolymer, which is a copolymer of a monomer mixture comprising a (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group; and an isocyanate hardener, wherein the content of the monomer (B) having an acidic group is 0.01 mass% or more and 6 mass% or less in 100 mass% of the monomer mixture, the content of the monomer (C) having a hydroxyl group is 0.05 mass% or more and 10 mass% or less in 100 mass% of the monomer mixture, and the gel fraction is 55% or more.

[0314] In the embodiment of the present invention, for example, the following items are provided.

[0315] (Item 1)

[0316] An adhesive composition comprises: an acrylate copolymer, which is a copolymer of a monomer mixture comprising a (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group; and an isocyanate hardener, wherein the content of the monomer (B) having an acidic group is 0.01% by mass or more and 6% by mass or less in 100% by mass of the monomer mixture, the content of the monomer (C) having a hydroxyl group is 0.05% by mass or more and 10% by mass or less in 100% by mass of the monomer mixture, and the gel fraction is 55% or more.

[0317] (Item 2)

[0318] The adhesive composition according to item 1, wherein the content of the (meth)acrylic acid alkyl ester monomer (a1) having an alkyl group with 8 to 12 carbon atoms in 100% by mass of the (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms is 55% by mass or more.

[0319] (Item 3)

[0320] The adhesive composition according to item 1, wherein the value of the ratio (P) of the loss elastic coefficient at 25° C. and the loss elastic coefficient at 150° C. measured at 1 Hz represented by Formula 1 is 0.02 or more and 0.3 or less.

[0321] P = (loss elastic coefficient at 150°C when measured at 1 Hz) / (loss elastic coefficient at 25°C when measured at 1 Hz) (Formula 1)

[0322] (Item 4)

[0323] An adhesive sheet includes a substrate and an adhesive layer including a cured product of the adhesive composition according to any one of items 1 to 3.

[0324] (Item 5)

[0325] An adhesive composition comprises: an acrylate copolymer, wherein the acrylate copolymer is a copolymer of a monomer mixture comprising a (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group; and an isocyanate hardener,

[0326] The content of the (meth)acrylic acid alkyl ester monomer (a1) having an alkyl group with 8 to 12 carbon atoms in 100% by mass of the (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms is 55% by mass or more and 90% by mass or less,

[0327] The content of the monomer (B) having an acidic group is 0.01% by mass or more and 6% by mass or less in 100% by mass of the monomer mixture,

[0328] The content of the monomer (C) having a hydroxyl group is 0.05% by mass or more and 10% by mass or less in 100% by mass of the monomer mixture,

[0329] The isocyanate curing agent includes a trimethylolpropane adduct of toluene diisocyanate.

[0330] The gel fraction is 55% or more and 98% or less, and

[0331] The value of the ratio (P) of the loss elastic coefficient at 25° C. and the loss elastic coefficient at 150° C. measured at 1 Hz represented by Formula 1 is 0.04 or more and 0.07 or less.

[0332] P = (loss elastic coefficient at 150°C when measured at 1 Hz) / (loss elastic coefficient at 25°C when measured at 1 Hz) (Formula 1)

[0333] (Item 6)

[0334] An adhesive sheet comprises a substrate and an adhesive layer comprising a cured product of the adhesive composition according to item 5.

[0335] Although the present invention has been described with reference to the above-described embodiments, the present invention is not limited to the above-described embodiments. The structure and details of the present invention can be variously modified within the scope of the present invention.

[0336] The disclosure of the present application is related to the subject matter described in Japanese Patent Application No. 2022-90061 filed on June 2, 2022, and all of the disclosed contents are incorporated herein by reference.

Claims

1. An adhesive composition comprising: an acrylate copolymer, wherein the acrylate copolymer is a copolymer of a monomer mixture comprising a (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms, a monomer (B) having an acidic group, and a monomer (C) having a hydroxyl group; and an isocyanate hardener, The content of the (meth)acrylic acid alkyl ester monomer (a1) having an alkyl group with 8 to 12 carbon atoms in 100% by mass of the (meth)acrylic acid alkyl ester monomer (A) having an alkyl group with 1 to 12 carbon atoms is 55% by mass or more and 90% by mass or less, The content of the monomer (B) having an acidic group is 0.01% by mass or more and 6% by mass or less in 100% by mass of the monomer mixture, The content of the monomer (C) having a hydroxyl group is 0.05% by mass or more and 10% by mass or less in 100% by mass of the monomer mixture, The isocyanate curing agent includes a trimethylolpropane adduct of toluene diisocyanate. The gel fraction is 55% or more.

2. The adhesive composition according to claim 1, wherein the value of the ratio (P) of the loss elastic coefficient at 25° C. to the loss elastic coefficient at 150° C. measured at 1 Hz represented by Formula 1 is 0.02 or more and 0.3 or less, P=(loss elastic coefficient at 150° C. when measured at 1 Hz) / (loss elastic coefficient at 25° C. when measured at 1 Hz) (Formula 1).

3. The adhesive composition according to claim 1 or 2, wherein the value of the ratio (P) of the loss elastic coefficient at 25°C to the loss elastic coefficient at 150°C when measured at 1 Hz represented by Formula 1 is 0.03 or more and 0.15 or less, P=(loss elastic coefficient at 150° C. when measured at 1 Hz) / (loss elastic coefficient at 25° C. when measured at 1 Hz) (Formula 1). 4 . An adhesive sheet comprising a substrate and an adhesive layer comprising a cured product of the adhesive composition according to claim 1 .